Resonant Raman scattering of graphite intercalation compounds KC8, KC24, and KC36. (2nd February 2014) - Wang, Yu; Puech, Pascal; Gerber, Iann; Pénicaud, Alain
<x xml:space="preserve">Abstract</x> Graphite intercalation compounds, due to charge transfer between layers of graphite and intercalants, have a strongly shifted Fermi level. Potassium is known to give its electron leading to a large charge transfer fc close to <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4svczrj3" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />−18</alternatives> for stage 1 (KC8) and <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4svczrp9" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />−124</alternatives> for stage 2 (KC24). The question is more subtle in stage 3 (KC36) for which the graphene layers are not equivalent. For stage 3, two Raman G bands are clearly visible, corresponding to the interior layer and the boundary layers, respectively. By varying the excitation energy from UV to infrared, we observe that the intensity of the boundary layers G band versus that of the interior layer is maximum at 2.5 eV, leading to a sharp resonance profile at room temperature. Using first‐principle calculation, we associate this transition to π → π∗ of the bounding layers. Copyright © 2014 John Wiley & Sons, Ltd.